Standards of Liability for Anti-Competitive Agreements: European Experience and Ukrainian Realities - Shvydka, Tetyana (Problems of legality, 2026)
The relevance of the study arises from differences in standards of liability for concerted anticompetitive actions under the law of Ukraine and the law of the European Union. National practice primarily focuses on establishing coordinated conduct between undertakings. The economic context and market effects are assessed to a limited extent. The European approach requires evaluation of the nature of the restriction of competition, market structure, actual or potential effects on competition, and proportionality of sanctions. These differences affect evidentiary standards and the determination of liability. The purpose of the article is to define contemporary standards of liability for concerted anticompetitive actions based on European practice and to formulate proposals for their application in national enforcement. The research methods include comparative legal analysis, formal legal interpretation, systemic analysis, and economic and legal assessment of market effects. Decisions of competition authorities and court practice were examined. The study establishes that the European standard of liability is based on the assessment of restriction of competition in light of the economic context and the role of each participant. It is demonstrated that national practice insufficiently accounts for market effects and the individual contribution of the undertaking. The article substantiates the need for a differentiated standard of proof depending on the type of conduct, market characteristics, and degree of impact on competition. Further research should focus on developing methodologies for economic analysis and criteria for individualizing sanctions.